Combination of competitive exclusion and immunisation with a live Salmonella vaccine in newly hatched chickens: immunological and microbiological effects - Braukmann, M.; Barrow, P.A.; Berndt, A.; Methner, U. (Elsevier, 2016)
In addition to evaluating the efficacy potential of a combined use of vaccination and competitive exclusion (CE) against Salmonella exposure in chicks at 3-days of age, a live Salmonella Enteritidis vaccine (SE-LV) and a CE culture were tested for their ability to induce parameters of the innate immunity. Whereas the invasive SE-LV induced an influx of granulocytes and macrophages aswell as an increased transcription of several cytokines in the caecalmucosa, the CE culture did not demonstrate any differences in these parameters compared to controls. It is therefore highly probable that the effects observed with CE cultures are not due to the rapid stimulation of the immune system. The combined use of both preparations did not result in an additive intestinal exclusion effect of the challenge strain more pronounced than that after single administration of the CE culture. The combined use of the Salmonella live vaccine and the CE culture resulted in an additive protective effect and prevented completely the systemic dissemination of the Salmonella challenge strain. To exploit the potential of combined use of CE and vaccination further and most effectively, live Salmonella vaccines are needed that are despite their attenuation in virulence still capable to induce both intestinal colonisation- and invasioninhibition effects against Salmonella exposure.